Resistance, Resilience, and Recovery Time of Grasslands in Response to Different Drought Patterns - Huilin Yu; Lin Zhu; Xinrui He; Yun Chen; Yishu Zhu; Futian Liu (Remote Sensing)
Resistance, resilience, and recovery time are critical for quantifying the stability of grasslands in response to drought disturbances. Few studies have simultaneously considered both drought intensity and duration to analyze the stability of different grassland types, which may overlook short-term extreme or long-term cumulative effects. This study used the monthly Standardized Precipitation Evapotranspiration Index (SPEI) to identify distinct drought patterns in Inner Mongolia, China, from 1998 to 2020, accounting for both intensity and duration. Grassland stability was assessed using monthly SPOT-VGT Normalized Difference Vegetation Index (NDVI) data. We focused on the vegetation response to short-term climate changes while minimizing the influence of seasonal fluctuations in vegetation growth. Six drought patterns were identified, and the resistance of grassland types under the same drought pattern followed this order: temperate desert steppe (TDS) > temperate typical steppe (TTS) > temperate meadow steppe (TMS). Resilience was ranked as TDS < TTS < TMS, while recovery time followed the reverse trend: TDS > TTS > TMS. A trade-off was observed between resilience and resistance. Most grasslands were able to recover within five months following a drought. These findings provide scientific support for enhancing ecosystem adaptability to climate change and for managing grassland resources more effectively.